CIVILITY VS SAVAGERY: MITIGATING VIOLENCE IN YASMINA REZA’S GOD OF CARNAGE - Eko Rujito Dwi Atmojo (Universitas Negeri Yogyakarta, 2024)
Violence plays a central role in Yasmina Reza's God of Carnage, a play that offers a profound look into human nature within the framework of today's society. The play reveals the underlying brutality masked by superficial politeness, showing how civilized behaviour can quickly descend into chaos. The study therefore aims to uncover the layers of violence and show how the characters mitigate the violence inherent in their nature. Through the interactions of two couples, the study shows that beneath their polite surfaces lies a primal instinct of aggression, suggesting that humans have an innate tendency towards violence. The characters' conflicts escalate from a seemingly trivial quarrel over their children to explosive confrontations that reveal deeper frustrations and anxieties. The work highlights the fragility of social etiquette, suggesting that politeness is merely a thin layer over inherent barbarism. Ultimately, God of Carnage assumes that violence is an integral part of human nature, reinforced by societal pressures and expectations. The work invites the audience to ponder the duality of human behaviour and ask whether true decency can fully restrain our violent impulses, or whether we are fundamentally ruled by our wild instincts.